Organizacja wirtualna jako twór nowoczesnej technologii - Nycz, Małgorzata; Smok, Barbara (Virtual organization as a product of modern technology, 2006)
The 21lh century brings new challenges for communities. Development of global information network enables fast data exchange between enterprises, international financial institutions as well as between people. Dynamically developing market and technology is one of the most significant features of the global economy. The 21lh century is called ‘knowledge and information age’ where the factors connected with appropriate knowledge as well as modern technologies usage decide about the market advantage. New processes and phenomena in its environment influence the enterprise. Dynamically changing environment requires new approach to management and new organization of the enterprise. It can be assured by the virtual organizations. The paper presents relations between modern technologies and virtual organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 215-224